2004
DOI: 10.1002/art.20655
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced neutrophil extravasation and rapid progression of proteoglycan‐induced arthritis in TSG‐6–knockout mice

Abstract: Objective. To gain insight into the mechanisms of the antiinflammatory effect of tumor necrosis factor ␣ (TNF␣)-induced protein 6 (Tnfip6) in arthritis, using Tnfip6-deficient animals.Methods. TNF␣-stimulated gene 6 (TSG-6) coding for Tnfip6 was disrupted. Tnfip6-deficient mice were backcrossed into proteoglycan-induced arthritis (PGIA)-susceptible BALB/c mice, and arthritis was induced by systemic immunization with cartilage proteoglycan (PG). Thioglycollate-induced sterile peritonitis was also assessed, to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 35 publications
5
55
0
Order By: Relevance
“…The formation of cross-linked HA networks at the surface of synovium and cartilage could serve to protect these tissues during inflammation by providing a barrier to prevent the loss of matrix components and perhaps acting as a temporary scaffold to direct and enhance formation of new matrix. This hypothesis, although speculative, is consistent with the anti-inflammatory properties of TSG-6, which has been shown to be highly protective of cartilage matrix and enhances its repair in mouse models of rheumatoid arthritis [19,28]. Although this protective activity also involves other functions of TSG-6 (i.e.…”
Section: Ha Cross-linking In Inflammationsupporting
confidence: 73%
“…The formation of cross-linked HA networks at the surface of synovium and cartilage could serve to protect these tissues during inflammation by providing a barrier to prevent the loss of matrix components and perhaps acting as a temporary scaffold to direct and enhance formation of new matrix. This hypothesis, although speculative, is consistent with the anti-inflammatory properties of TSG-6, which has been shown to be highly protective of cartilage matrix and enhances its repair in mouse models of rheumatoid arthritis [19,28]. Although this protective activity also involves other functions of TSG-6 (i.e.…”
Section: Ha Cross-linking In Inflammationsupporting
confidence: 73%
“…We have shown that TSG-6 deficiency leads to decreased airway eosinophilia. In contrast, other investigators have shown that TSG-6 deficiency has an enhancing effect on neutrophil migration into peripheral joints of mice undergoing a murine model of proteoglycan-induced arthritis (46). Reciprocally, exogenous TSG-6 inhibits neutrophil extravasation in a murine model of acute inflammation (47).…”
Section: Discussionmentioning
confidence: 76%
“…Veterinary care of the mice and the related animal experiments was approved by the University of Illinois Animal Resources Center. The TSG6 knockout mice originally generated on a BALB/c background (30) were obtained from Jackson Laboratory. Age-matched TSG6 +/+ and TSG6…”
Section: Methodsmentioning
confidence: 99%
“…Human and murine TSG6 proteins are ∼94% identical (4). Transgenic mice overexpressing TSG6 were resistant to collageninduced arthritis (CIA) (9), whereas inactivation of the TSG6 gene enhanced inflammation and increased the susceptibility to arthritis (30). Intravenous administration of MSCs in mice also prevented endotoxin-mediated ALI, apparently by reducing the expression of proinflammatory cytokines and neutrophil sequestration in lungs (13); however, siRNA-mediated suppression of TSG6 expression in MSCs prevented these protective effects, indicating the involvement of TSG6 in this protection.…”
Section: Tsg6 Treatment Prevents Lps-induced Lung Vascular Injury Nementioning
confidence: 99%